2017
DOI: 10.2140/gt.2017.21.3093
|View full text |Cite
|
Sign up to set email alerts
|

Kato–Nakayama spaces, infinite root stacks and the profinite homotopy type of log schemes

Abstract: For a log scheme locally of finite type over C, a natural candidate for its profinite homotopy type is the profinite completion of its Kato-Nakayama space [26]. Alternatively, one may consider the profinite homotopy type of the underlying topological stack of its infinite root stack [48]. Finally, for a log scheme not necessarily over C, another natural candidate is the profiniteétale homotopy type of its infinite root stack. We prove that, for a fine saturated log scheme locally of finite type over C, these t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 39 publications
(74 reference statements)
1
38
0
Order By: Relevance
“…Let us show how the functorial interpretation of Theorem 3.2 gives a globally defined morphism of topological stacks X log → n √ X top for every n, and these assemble into a morphism of pro-topological stacks X log → ∞ √ X top . We will check later (see Proposition 4.6) that this morphism coincides with the one constructed in [CSST,Proposition 4.1].…”
Section: The Kato-nakayama Space As a "Root Stack"mentioning
confidence: 61%
See 2 more Smart Citations
“…Let us show how the functorial interpretation of Theorem 3.2 gives a globally defined morphism of topological stacks X log → n √ X top for every n, and these assemble into a morphism of pro-topological stacks X log → ∞ √ X top . We will check later (see Proposition 4.6) that this morphism coincides with the one constructed in [CSST,Proposition 4.1].…”
Section: The Kato-nakayama Space As a "Root Stack"mentioning
confidence: 61%
“…Building on this idea, in the paper [CSST] by Carchedi, Scherotzke, Sibilla and the first author it is shown that there is a canonical morphism Φ X : X log → ∞ √ X top from the Kato-Nakayama space to the topological realization of the infinite root stack of X, that is moreover a "profinite equivalence". In that paper the morphism is constructed locally on X, in presence of a Kato chart for the log structure, and then globalized by gluing [CSST,Section 4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore for every i we have j a ij b j = 0 in B. Now using the description of B given by (6), let us write…”
Section: Consider the Sheaf Amentioning
confidence: 99%
“…The use of the Kato-Nakayama space X log is heuristically justified by the fact that the infinite root stack is a sort of "profinite algebraic incarnation" of the former: there is a morphism X log → ∞ √ X top to the topological realization of ∞ √ X, which is a "profinite equivalence" [6,Theorem 6.4]. The fiber of X log → X over a point x can be identified with a real torus (S 1 ) r , and the fiber of ∞ √ X top → X with B Z r , where r is the "rank of the log structure" at x.…”
Section: Introductionmentioning
confidence: 99%